PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA (STUDI PADA KABUPATEN DAN KOTA DI PROVINSI NUSA TENGGARA BARAT) - IRIANTO IRIANTO; BAIQ KISNAWATI; ISTIARTO ISTIARTO; BQ.ERTIN HELMIDA (Universitas Mahasaraswati K. Mataram, 2021)
This study aims to determine the effect of local revenue, general allocation funds, specific allocation funds, and capital expenditures on the human development index in districts and cities in West Nusa Tenggara province. This type of research is classified as associative, where there are four independent variables (local revenue, general allocation funds, special allocation funds and capital expenditures) and one dependent variable, namely the human development index. The population used was local government financial reports consisting of ten districts / cities in a period of seven years from 2013-2019 (total population used was 70). The data used in this research were secondary data. The data analysis used were multiple regression analysis. The results showed that partially the original regional income and general allocation funds had an effect on the human development index, while the special allocation funds and capital expenditures had no effect on the human development index. Simultaneously local revenue, general allocation funds, special allocation funds and capital expenditures affect the human development index.